Evaluation of the quality constructs of a tax management system based on DeLone and McLean IS success model. (2nd January 2023) - Akrong, Godwin Banafo; Shao, Yunfei; Owusu, Ebenezer
ABSTRACT: We presented a novel method to analyze the impact tax management systems have on users (individual impact) in this study. The interrelationship among the three information system (IS) quality constructs is examined. The study is based on the evaluation undertaken in this paper of DeLone and Mclean's (D & M) model. Quantitative data are gathered from a related Ghanaian enterprise. The structural equation modelling of partial least squares was utilized to model the system quality, information quality, and service quality. The result of the study shows that the three quality constructs of the D & M model positively influence the users of a tax management system (individual impact). The results also show that there is a significant positive interrelation among the IS quality constructs.